Penguatan Daya Saing UKM Pada Usaha Makanan Khas Daerah Sumatera Barat - Fisla Wirda; Herizon; Trimardi Putra (Universitas Lancang Kuning, 2020)
Capability of management is a determinant of business competitiveness. One of the problems of SMIs in Indonesia is the weakness of managerial capabilities of entrepreneurs, so that many businesses arise but at the same time there are manybusiness are collaps. Community service activities aim to keep the IKM survival on business competition. The partners that are fostered are the Dakak-Dakak Bundo Pariangan Business and the Tungku Dakak-Dakak Nila Business. Both partners produce and sell Dakak-dakak cakes, which are special foods of the Simabur region, Pariangan sub-district, Tanah Datar Regency, West Sumatra. The problems of the partners at production side are: not have production machines and PIRT certificates and halal certificates from MUI. While from the management aspect is packaging that is still simple using ordinary plastic which is tied to a rubber band at the end, a store display whose arrangement is less attractive. The method of implementing activities is in the form of training and coaching that is carried out for eight months. The results of the activities include providing rice milling machines accompanied by training in use, repairs and maintenance, publishing of Home Industry Food Certificates (PIRT), Halal certificates from the Indonesian Ulema Council, making good packaging and brands, layouts by displaying storefronts so that the store display is visible interesting.